Quantitative analysis of the intra- and inter-subject variability of the whole salivary proteome - Jehmlich, N.; Dinh, K. H. D.; Gesell-Salazar, M.; Hammer, E.; Steil, L.; Dhople, V. M.; Schurmann, C.; Holtfreter, B.; Kocher, T.; Völker, U. (Journal of periodontal research, 2013)
Background and Objective Interest in human saliva is increasing for disease‐specific biomarker discovery studies. However, protein composition of whole saliva can grossly vary with physiological and environmental factors over time and it comprises human as well as bacterial proteins. Material and Methods We compared intra‐ and inter‐subject variabilities using complementary gel‐based (two‐dimensional difference gel electrophoresis, 2‐D DIGE) and gel‐free (liquid chromatography tandem mass spectrometry, LC‐MS/MS) proteomics profiling of saliva. Unstimulated whole saliva of four subjects was examined at three different time‐points (08.00 h, 12.00 h and 17.00 h) and variability of the saliva proteome was analyzed on two successive days by LC‐MS/MS. Results In the 2‐D DIGE experiment, the median coefficient of variation (CV) for intra‐subject variability was significantly lower (CV of 0.39) than that for inter‐subject variability (CV of 0.57; CV of technical replicates 0.17). LC‐MS/MS data confirmed the significantly lower variation within subjects over time (CV of 0.37) than the inter‐subject variability (CV of 0.53; CV of technical replicates 0.11), and that the inter‐subject variability was not time‐dependent. Conclusion Both techniques revealed similar trends of variations on technical, intra‐ and inter‐subject level but provided peptide and protein focused information and should thus be used as complementary approaches. The data presented indicate that 2‐D DIGE as well as LC‐MS/MS approaches are suitable for biomarker screening in saliva.